Clinical profile, causes, and outcomes of optic neuritis at Groote Schuur Hospital - Mustak, Sayeed-Hamzah (Division of Ophthalmology, 2017)
Objective: To determine the clinical profile, causes and response to corticosteroid therapy in patients admitted and treated for optic neuritis at a tertiary hospital in Cape Town, South Africa. Methods: A retrospective case review was conducted of 117 patients admitted to Groote Schuur Hospital and treated for optic neuritis between January 2002 and December 2012. Inclusion criteria were based on clinical findings of acute optic nerve dysfunction with or without optic disc swelling. Demographic information, clinical presentation, course of illness, investigations performed and visual outcomes at discharge and at three month follow up were collected. Data analysis was performed using STATA version 10.0. Results: 60 of 117 patients (51%) had an identifiable secondary cause for optic neuritis. Of the 57 patients with idiopathic optic neuritis only 14 had features of "typical optic neuritis" associated with demyelinating disease. HIV and syphilis accounted for 62% of secondary causes of optic neuritis. Presenting visual acuity of hand movements (HM) or worse and absence of pain with extra ocular movement were associated with poorer final visual outcomes in the idiopathic optic neuritis group. Conclusion: Optic neuritis in our patients, as elsewhere in Africa,tends to be atypical in presentation, with a high proportion of patients having an identifiable, most commonly infectious, cause.These patients thus require more extensive investigation in order to identify possible causes which may influence management. In settings with a high HIV prevalence, HIV and syphilis testing should form part of the routine first line investigations for patients with optic neuritis.Secondary optic neuritis and idiopathic atypical optic neuritis carry a poorer prognosis than typical demyelinating optic neuritis.